A Qualitative Analysis of the South African Just Transition - Monteith, Struan (School of Economics, 2021)
The threat of climate change has been identified as one of the leading challenges facing humanity. As such, there is a necessary global transition to lower-carbon economies and societies to reduce the harmful emissions caused by human activities to mitigate the growing climate crisis. Yet, there are fears that there will be job losses and economic hardships as the world transitions away from the carbonheavy dependence of the past. The Just Transition principle has emerged globally as a framework of ensuring these potential job losses and economic hardships are planned for, and the people inherently at risk in the transition are protected. The Just Transition is built on the acknowledgement that climate change must be averted, but it must be done so justly. In South Africa, there is a particular need for the Just Transition, based on the country's historic dependence on coal, the broad socioeconomic challenges and the country's vulnerability to climate change. This thesis explores hundreds of qualitative views from numerous stakeholders around the country on what the Just Transition will mean for South Africa. It analyses the current Mineral Energy Complex and climate change situation in South Africa, and examines the stakeholder determined vision for the country for 2050. Synthesised from views from across South Africa, this thesis furthermore established the four interrelated and stakeholder determined pathways which could facilitate the South African Just Transition – namely an Energy Transition, Restoring Land Resources, providing Safe Water for All, and utilising Green Growth.